2017
DOI: 10.1139/apnm-2016-0301
|View full text |Cite
|
Sign up to set email alerts
|

Mixed compared with single-source proteins in high-protein diets affect kidney structure and function differentially in obesefa/faZucker rats

Abstract: Questions remain regarding the potential negative effects of dietary high protein (HP) on kidney health, particularly in the context of obesity in which the risk for renal disease is already increased. To examine whether some of the variability in HP effects on kidney health may be due to source of protein, obese fa/fa Zucker rats were given HP (35% of energy from protein) diets containing either casein, soy protein, or a mixed source of animal and plant proteins for 12 weeks. Control lean and obese rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…High protein diets have been shown to worsen albuminuria in otherwise healthy rats [ 26,27 ] and mice. [ 28–31 ] The current study observed an increase in renal hypertrophy, consistent with some, [ 26,27,32,33 ] but not all [ 34 ] previous animal studies. In this study we observed an upregulation of NFĸB p65 mRNA in the kidney cortex with high protein diet feeding.…”
Section: Discussionsupporting
confidence: 93%
“…High protein diets have been shown to worsen albuminuria in otherwise healthy rats [ 26,27 ] and mice. [ 28–31 ] The current study observed an increase in renal hypertrophy, consistent with some, [ 26,27,32,33 ] but not all [ 34 ] previous animal studies. In this study we observed an upregulation of NFĸB p65 mRNA in the kidney cortex with high protein diet feeding.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, despite numerous studies that found that an HP diet increases GFR ( 30 , 33 , 49 , 53 , 70 , 71 ), to date there is no evidence linking HP intake to kidney disease in healthy individuals or those at risk of kidney disease due to pre-existing conditions such as obesity, hypertension, or dyslipidemia ( 62 ). Furthermore, animal studies have shown that markers of renal damage do not differ in obese rats fed a high-mixed-protein diet for 12 wk as compared with those fed a lower-protein diet, despite an increase in kidney size ( 72 ). In addition, monocyte chemoattractant protein 1 (MCP-1) concentration, a known mediator of kidney disease susceptibility ( 73 ), was lower in the high-mixed-protein group ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies have shown that markers of renal damage do not differ in obese rats fed a high-mixed-protein diet for 12 wk as compared with those fed a lower-protein diet, despite an increase in kidney size ( 72 ). In addition, monocyte chemoattractant protein 1 (MCP-1) concentration, a known mediator of kidney disease susceptibility ( 73 ), was lower in the high-mixed-protein group ( 72 ). These animal data again highlight that increased kidney size and GFR are not linked to kidney damage and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Deficient intake of macronutrients can cause several problems, such as reduced energy, growth defects, hypoglycemic seizures, and liver or heart damage (1-3). On the other hand, high-sugar intake possibly leads to decreased insulin sensitivity, high-protein consumption leads to kidney disease, and a high-fat diet can cause chronic inflammation, which itself can lead to type 2 diabetes (4)(5)(6)(7)(8). While many known regulators of food intake have been implicated in affecting macronutrient consumption, such as neuropeptide Y (NPY), proopiomelanocortin, and galanin, this topic has been difficult to study and various research groups have used different conditions for testing macronutrient selection (9)(10)(11).…”
mentioning
confidence: 99%